2005
DOI: 10.1373/clinchem.2005.056721
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Nanogram Amounts of Total RNA by the SMART-Based PCR Method for High-Density Oligonucleotide Microarrays

Abstract: The SMART (switching mechanism at the 5Ј end of RNA templates of reverse transcriptase) method (1, 2 ), in combination with PCR, has been used to amplify minute samples obtained from sources such as laser capture microdissections and biopsies for gene expression analysis using oligonucleotide microarray gene chip technology (3-7 ). Amplifications Ͼ10 5 -fold can be achieved in a short time. However, reports in the literature have rarely discussed the feasibility and reproducibility of PCR-based methods when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Other aspects of target preparation can also introduce sources of variation that can affect the correlation between datasets. Reverse transcriptases can vary in their ability to yield useful amounts of cDNA from limiting amounts of RNA [43] and in their ability to generate cDNA that largely maintains the length of the original transcript, an important issue when using oligonucleotide-based microarrays (see later). Comparison of DNA hybridizations (unamplified and PCR), with fragmented aRNA hybridizations (IVT), may also introduce variation due to different hybridization kinetics [44].…”
Section: Resultsmentioning
confidence: 99%
“…Other aspects of target preparation can also introduce sources of variation that can affect the correlation between datasets. Reverse transcriptases can vary in their ability to yield useful amounts of cDNA from limiting amounts of RNA [43] and in their ability to generate cDNA that largely maintains the length of the original transcript, an important issue when using oligonucleotide-based microarrays (see later). Comparison of DNA hybridizations (unamplified and PCR), with fragmented aRNA hybridizations (IVT), may also introduce variation due to different hybridization kinetics [44].…”
Section: Resultsmentioning
confidence: 99%
“…Genes transcribed at low levels, such as regulatory proteins, exert large biological effects from small changes in expression level [13,18,22]. Considerable work with enzymatic amplification, including PCR-based [23][24][25][26][27][28][29][30][31][32][33], multiple displacement amplification-based (MDA) [24,, and RNA polymerase-based [23,[56][57][58][59][60][61][62][63] protocols, has enabled the use of hybridization microarrays and sequence tag methods to characterize low abundance mRNA samples [64][65][66][67][68][69][70][71][72]. This includes several recent reports of message profiling of single cells [73][74][75][76][77][78][79][80][81][82].…”
Section: Quantifying Gene Expression From Very Small Samplesmentioning
confidence: 99%
“…Single cell transcript profiling studies have found that only large magnitude changes in expression can be quantified for moderate-and low-abundance transcripts [24,27,28,30,35 , 41 , 46 , 57 , 62 ,63,67,83-88]. In several papers, Nygarrd et al [85,88] have argued strongly that fundamental, stochastic effects prevent reliable enzymatic amplification of all species from minute samples; they conclude that high and medium abundance species can be quantitatively amplified, but low copy number species will always be amplified unevenly.…”
Section: Critical Limitations Of Enzymatic Amplificationmentioning
confidence: 99%